2020
DOI: 10.1002/1878-0261.12782
|View full text |Cite
|
Sign up to set email alerts
|

In vivo anti‐V‐ATPase antibody treatment delays ovarian tumor growth by increasing antitumor immune responses

Abstract: Tumor acidity is the key metabolic feature promoting cancer progression by eliciting immune‐suppression. V‐ATPases on a cancer cell's surface pump out excess protons and acidify the tumor microenvironment (TME). In vivo treatment of ovarian tumors using a monoclonal antibody (a2v‐mAb) directed against V‐ATPase‐V0a2 delays tumor growth by enhancing antitumor immune responses, making it an effective treatment strategy in ovarian cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…The blue scale color map represents the number of publications where a specific isoform overexpression was reported. This heatmap was built based on the following publications 50,83,85,87,89,91,93,96,99–101,103–123 . CNS, central nervous system; mRNA, messenger RNA [Color figure can be viewed at wileyonlinelibrary.com]…”
Section: V‐atpases: Attractive Targets For a Multitude Of Human Diseasesmentioning
confidence: 99%
“…The blue scale color map represents the number of publications where a specific isoform overexpression was reported. This heatmap was built based on the following publications 50,83,85,87,89,91,93,96,99–101,103–123 . CNS, central nervous system; mRNA, messenger RNA [Color figure can be viewed at wileyonlinelibrary.com]…”
Section: V‐atpases: Attractive Targets For a Multitude Of Human Diseasesmentioning
confidence: 99%
“…This approach is facilitated by the fact that the extracellular domains have been clearly defined both through biochemistry [141] and through structural analysis using cryo-electron microscopy [62]. A recent report showed that monoclonal antibodies against the V-ATPase a2 subunit delayed ovarian tumor growth [142]. The inhibitory antibody was generated against amino acids 488-510 in human a2, which the authors stated is in the "transmembrane region of the protein" [143].…”
Section: The Potential Of A3 As a Therapeutic Target For Osteolytic Diseasesmentioning
confidence: 99%
“… 38 39 These molecules play significant roles in mediating an immune suppressive microenvironment in the tumor and ATPases are identified as promising targets for immunotherapy and combination therapy to combat tumors. 40 41 Kulshrestha et al showed that V-ATPase inhibition using a monoclonal antibody enhances the antitumor immune response, drastically inhibiting ovarian tumor growth without evident side effects. 40 Our previous study demonstrated that MET interacts with V-ATPase and suppresses liver cancer immunogenicity through the activation of the mammalian target of rapamycin.…”
Section: Discussionmentioning
confidence: 99%
“… 40 41 Kulshrestha et al showed that V-ATPase inhibition using a monoclonal antibody enhances the antitumor immune response, drastically inhibiting ovarian tumor growth without evident side effects. 40 Our previous study demonstrated that MET interacts with V-ATPase and suppresses liver cancer immunogenicity through the activation of the mammalian target of rapamycin. 41 Moreover, the V-ATPase inhibitor Con A significantly enhances the efficacy of chemotherapy-based vaccination in a mouse model.…”
Section: Discussionmentioning
confidence: 99%